Social Critique of Consumerism in Nizar Qabbani’s Poem Habibati Tas’aluni (حبيبتي تسألني): A Sociological Perspective of Literature - Qirany, Yunia Eka Al (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study examines the social critique of the phenomenon of consumerism in the poem “Habibati Tas’aluni” (My Beloved Asks Me) by Nizar Qabbani through the perspective of literary sociology. As a poet who witnessed the Arab cultural transition toward modernity, Qabbani captured the anxiety over the erosion of human values by the tide of materialism. The central issue in this study is how consumerism dictates the way people interact, where identity is no longer constructed through character but through material possessions. Using descriptive qualitative methods and a literary sociology approach, this study analyzes the text as a reflection of sociocultural reality. The findings reveal that Qabbani launches a sharp critique against three aspects: first, the commodification of emotions, where love is trapped within transactional logic; second, the trivialization of existential meaning, which prioritizes external (artificial) appearances over spiritual depth; and third, the alienation of modern humans who lose their freedom due to commodity fetishism. This poem functions not only as an aesthetic expression but also as a social document that challenges dehumanization in a consumerist society. These findings affirm Qabbani’s use of romantic metaphors to address broader socio-economic issues, positioning love as the last bastion against an increasingly materialistic world.